2008
DOI: 10.1016/s1472-6483(10)60142-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on IVF and ICSI outcome: a retrospective study

Abstract: A group of 140 women with a body mass index (BMI) < or = 24 kg/m(2) undergoing 291 cycles was compared with a group of 138 women with a BMI >24 kg/m(2) in 291 cycles, with respect to duration of ovarian stimulation and dose of gonadotrophin, number of oocytes collected, cleavage and implantation rate, clinical pregnancy, miscarriage and delivery rates. Patients with a BMI > 24 kg/m(2) demonstrated a significant decrease in the number of follicles after stimulation (P = 0.01), a comparative increase in the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 22 publications
6
60
1
1
Order By: Relevance
“…This issue remains controversial, with studies reporting either higher odds of miscarriage in overweight and obese patients regardless of the method of conception (22,43) or no adverse effect of the extremes of BMI on the pregnancy outcome in IVF patients (27,(48)(49)(50)(51)(52) or on donor egg recipients (29,53). Similarly, we found no difference in the SAB rates among the different groups.…”
Section: Discussionmentioning
confidence: 42%
“…This issue remains controversial, with studies reporting either higher odds of miscarriage in overweight and obese patients regardless of the method of conception (22,43) or no adverse effect of the extremes of BMI on the pregnancy outcome in IVF patients (27,(48)(49)(50)(51)(52) or on donor egg recipients (29,53). Similarly, we found no difference in the SAB rates among the different groups.…”
Section: Discussionmentioning
confidence: 42%
“…The majority of those studies had much smaller sample sizes, ranging from 72 to 278, and used binomial BMI classifications (10,(25)(26)(27). Two other studies included only Asian patients and three BMI categories (28,29), and Dokras et al analyzed data only from patients <38 years old (30).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated decreased odds of CP in patients with higher BMI (9,10,16,31). However, many more studies have failed to identify a statistically significant difference (7,8,20,(25)(26)(27)(28)(29)(30), including two meta-analyses of 21 and 13 studies that demonstrated a lower chance of CP with obesity (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study of 50 overweight (BMI O26 kg/m 2 ) and 50 normal controls (BMI 18-25 kg/m 2 ) observed that fertilisation rate was significantly reduced in overweight women (46.2 vs 61.3%, P!0.05; Salha et al 2001). A more recent report has observed a more modest but statistically significant reduction in fertilisation rate in overweight women (BMI O24 kg/m 2 ) compared with normal women (BMI !24 kg/m 2 ), 51.7 vs 58.9% (Matalliotakis et al 2008). However, other reports have not observed a weight-related reduction in fertilisation rate (Wittemer et al 2000, Fedorcsak et al 2004, Dokras et al 2006, Esinler et al 2008, Bellver et al 2010.…”
Section: Obesity and The Oocytementioning
confidence: 95%
“…It is thought that this is the cumulative effect of lower implantation and pregnancy rates, higher miscarriage rates and increased obstetric complications (Bellver et al 2006). Whilst some authors have reported lower pregnancy and live birth rates in obese women undergoing assisted conception treatments (Wang et al 2000, Carrell et al 2001, Loveland et al 2001, Fedorcsak et al 2004, Bellver et al 2010, others have been unable to demonstrate reduction in success rates in obese women (Lashen et al 1999, Wittemer et al 2000, Dechaud et al 2006, Martinuzzi et al 2008, Matalliotakis et al 2008. A retrospective analysis of outcomes in 3586 patients undergoing IVF/ICSI/GIFT observed that the cumulative chance of achieving at least one pregnancy was significantly reduced in the obese women when compared to normal controls Wang et al 2000).…”
Section: Obesity and Assisted Conceptionmentioning
confidence: 99%